2020
DOI: 10.1293/tox.2020-0018
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac lesions in Duchenne muscular dystrophy model rats with out-of-frame <i>Dmd</i> gene mutation mediated by CRISPR/Cas9 system

Abstract: Short running head Cardiac changes in Duchenne muscular dystrophy model rats

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…In recent years, we have generated a rat model of DMD (DMD rats) using a CRISPR/Cas9 genome editing system. Our previous research showed that DMD rats exhibited more severe skeletal muscle damage and cardiomyopathy phenotypes than mdx mice 11 – 14 . In DMD rats, cardiac degeneration and fibrosis progress with age and overt left ventricular (LV) dysfunction occurs around 8–10 months old 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, we have generated a rat model of DMD (DMD rats) using a CRISPR/Cas9 genome editing system. Our previous research showed that DMD rats exhibited more severe skeletal muscle damage and cardiomyopathy phenotypes than mdx mice 11 – 14 . In DMD rats, cardiac degeneration and fibrosis progress with age and overt left ventricular (LV) dysfunction occurs around 8–10 months old 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…To confirm that Dm rats were deficient in dystrophin protein, soleus muscles from a WT or D m rat were immunostained with the dystrophin antibody previously used in our laboratory (supporting information Figure S3) (Miyamoto et al, 2020). Dystrophin is known to be expressed in the cerebral cortex, cerebellum, and hippocampus; however, little information regarding its expression in the brainstem is available.…”
Section: Resultsmentioning
confidence: 99%
“…The rat model showed pathological and pathophysiological changes in the heart in young adulthood, as commonly seen in human patients with DMD. For example, degeneration/necrosis of cardiomyocytes and myocardial fibrosis were prominent in the right ventricular wall and outer layer of the left ventricular wall at 3 months of age (Miyamoto et al, 2020). In addition, as background data, blood gas analysis revealed a low pH value (7.34) in D m rats, which suggested pathophysiological changes in the respiratory system.…”
Section: Introductionmentioning
confidence: 99%
“…These disease readouts were sufficient to include a therapeutic research arm, i.e., screening the efficiency of CRISPR/Cas9-mediated reframing or antisense oligo nucleotide (AON)-targeted exon skipping in all but one report [21]. Similar CRISPR/Cas9 approaches have been used to generate rat [26][27][28][29], rabbit [30] and non-human primate [31,32] models of dystrophinopathy that showed progressive heart involvement similar to those observed in humans.…”
Section: Genome-editing-based Models Of Dacmentioning
confidence: 99%